Pseudo Geometric Routing for Sensor Networks - Landsiedel, Olaf (Algorithms for Sensor and Ad Hoc Networks, 2007)
The first sensor network deployments mainly focused on data collection [274, 308]. Corresponding implementations [184, 161] commonly offer tree based routing, such as many-to-one and one-to-many communication patterns. Routing protocols to mention for this purpose are Directed Diffusion [194] and TAG [271]. These protocols build trees to broadcast commands from a base station to the sensor network and to collect and aggregate data along the path to the base station.